Biomimetic Synthesis of Isoindolinones Related to the Marilines - Augner, Daniel; Schmalz, Hans-Günther (Synlett, 2015)
The non-enzymatic formation of the racemic isoindolinone core structure during the biosynthesis of the marine natural products mariline A and B was mimicked by employing structurally closely related model substrates. Thus, condensation of 2-formyl-3,5-dimethoxy-4-methyl-acetophenone with different primary amines in the presence of AcOH afforded the isoindolinone products in up to 73% yield.
Keywords: natural products; biomimetic synthesis; heterocycles; isoindolinones; aromatic compounds.